Does Energy Consumption Impact The Environment? Evidence from Australia Using the JJ Bayer-Hanck Cointegration Technique and the Autoregressive Distributed Lag Test - Khanal, Avishek (International Journal of Energy Economics and Policy, 2021)
This study investigates the impact of energy consumption on environmental pollution in Australia using time series data from 1971 to 2015. Gross domestic product (GDP), total population (TP), and financial development (FD) are included as control variables. In achieving the objective, employ unit root test, cointegration test, and autoregressive distributed lag (ARDL) long-run and short-run methodology to examine the nexus between energy consumption, carbon dioxide (CO2) emissions, Gross Domestic Product (GDP), total population (TP), and financial development (FD). The results of ARDL long-run and short-run reveals that energy consumption is the most substantial determinant that impacts environmental pollution. However, the empirical findings suggest that GDP, TP, and FD are insignificant in contributing to an increase in CO2 emissions. Thus, this study concludes that policymakers and attention on energy consumption trend and pattern is crucial for effective policies on environmental pollution. Keywords: Electricity consumption, Carbon dioxide emissions, GDP, Bayer-Hanck (BH) cointegration technique, ARDL JEL Classifications: O13, Q43, Q54, Q56 DOI: https://doi.org/10.32479/ijeep.11163